Estrés y su influencia en el rendimiento laboral de un hombre de 30 años del cantón Arenillas - Llaguno Medina, Nayari Lilibeth (2022)
Stress problems are a feeling of physical and emotional tension that frequently occurs in people who are going through difficulties in the work, family and social areas. This case sudó aims to determine the relationship between stress and poor job performance of a 30-year-old man. In the investigative process, a descriptive-correlational study was carried out; For this reason, a conceptual and bibliographical analysis was applied that allowed us to delve deeper into each of the methods, techniques and variables proposed in the case study, to determine the root of the patient's problem, instruments such as: Dass-21 test with a score of 16 points that results in a severe stress level, the Perceived Stress Scale (PSS) with a score of 23 points that results in a record stress level. To establish the diagnosis, the criteria of the DSM-5 Guide were used. The results were: The patient's health problems arise from the transfer of work as a driver of heavy load trailers, he has a good relationship with his father, brothers and is estranged from his wife, he has difficulty concentrating, decreased sexual desire, decreased appetite and memory loss which makes it difficult to carry out your daily activities. By virtue of those detected, a therapeutic plan was proposed that will help overcome stress and improve their work performance and mental state.